REWARD-BASED MOTIVATION STRATEGY AND STUDENTS’ ACADEMIC ACHIEVEMENT IN PUBLIC SECONDARY SCHOOLS IN KIPKOMO SUB- COUNTY, KENYA - Kodokwang , Andrew; Kikechi, Ronald Werunga (IJRDO- Journal of Educational Research, 2023)
The purpose of the study was to assess the influence of reward-based motivation strategy on students’ academic achievement in public secondary schools in Kipkomo Sub- County, Kenya. It adopted a descriptive survey research design, with a target population of 597 persons. The sample size of 234 persons was determined using the Krejcie & Morgan Table (1970) for determining sample sizes. Data was collected using questionnaires and interview guides. The instruments were validated by experts in the area of study. Reliability of the instruments was determined through a pilot study where Spearman’s rank correlation coefficient (r) of the questionnaires was found to be 0.79, which implied that the instruments were reliable. Quantitative data was analyzed using descriptive statistics and presented in tables. Qualitative data was analyzed under common themes and presented in narratives. The study established reward-based motivation strategy influence students’ academic achievement in public secondary schools. It was therefore recommended that for enhanced students’ academic achievement, school Principals, school administration, policy makers and other stakeholders should consider using reward-based motivation strategy to improve students’ academic performance.